2013
DOI: 10.1074/jbc.m112.385682
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Glucagon Secretion in Normal and Diabetic Human Islets by γ-Hydroxybutyrate and Glycine

Abstract: Background: ␤-Cells regulate ␣-cells via paracrine mechanisms. Results: A GABA shunt defect impairs glucose suppression of glucagon secretion in diabetic human islets. Glucagon secretion is inhibited by ␥-hydroxybutyrate produced by ␤-cells but is stimulated by glycine via plasma membrane receptors. Conclusion: ␥-Hydroxybutyrate and glycine serve as counterbalancing receptor-based regulators of glucagon secretion. Significance: Amino acids and their metabolites are central regulators of ␣-cell function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
91
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(107 citation statements)
references
References 62 publications
13
91
1
2
Order By: Relevance
“…This has been attributed in part to declined intraislet insulin (21), decreased intraislet GABA levels (22), and/or reduced GABA receptor signaling (23). These reports are consistent with clinical observations that T2D patients have exaggerated glucagon responses under glucagon stimulatory conditions (24).…”
Section: Discussionsupporting
confidence: 79%
“…This has been attributed in part to declined intraislet insulin (21), decreased intraislet GABA levels (22), and/or reduced GABA receptor signaling (23). These reports are consistent with clinical observations that T2D patients have exaggerated glucagon responses under glucagon stimulatory conditions (24).…”
Section: Discussionsupporting
confidence: 79%
“…GlyR in human islets is recently reported to be expressed specifically in a-cells but not b-cells (35), supported by the finding that glycine stimulated glucagon but not insulin secretion from human islets. However, the experiments were performed in the absence of glucose, which leads to the activation of unphysiologically large K ATP currents in b-cells and may prevent any glycine effect on the membrane potential.…”
Section: Discussionsupporting
confidence: 54%
“…However, the experiments were performed in the absence of glucose, which leads to the activation of unphysiologically large K ATP currents in b-cells and may prevent any glycine effect on the membrane potential. Li et al (35) observed [Ca 2+ ] i responses upon glycine application in a subset of dispersed islet cells, but an unequivocal identification of the cell types was not performed. Our data clearly demonstrate that among human islet cells, GlyR and glycine-activated Cl -currents are most active in b-cells.…”
Section: Discussionmentioning
confidence: 99%
“…Triglycerides (TG) or free fatty acids in plasma or tissues were assayed with the Infinity TM triglyceride reagent kit or Biovision kit, respectively. Plasma insulin, glucagon (31), leptin, and adiponectin were determined using ELISA kits. Tissue protein was determined by Coomassie Blue (Thermo Scientific).…”
Section: Lc/ms/ms Gc-ms and Nmrmentioning
confidence: 99%